An innovative passive metallic damper with replaceable components for earthquake protection of structures - Reza Aghlara, 1975-, author; Mahmood Md. Tahir, 1962-, supervisor; Azlan Adnan, supervisor; Fakulti Kejuruteraan. Sekolah Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Thesis (Ph.D (Kejuruteraan Awam)) - Universiti Teknologi Malaysia, 2019